Communication & Culture interfaces - SOARES DA CUNHA REGINA SOARES DA CUNHA, SONIA REGINA; Silva, Prof. Dr. Lawrenberg Advincula da (Revista Comunicação, Cultura e Sociedade, 2024)
This issue of the Journal of Communication, Culture and Society (RCCS) presents articles by academics who have developed research on the relationship between Communication and Culture and their interfaces in various contexts. More and more, the most advanced studies in Communication have been showing how communication, which includes the most diverse socio-communicative processes – and a constant movement from means to mediations – has become a fundamental part of human life and plays a vital role in the way humanity interacts in society, as it primarily enables the exchange of ideas, beliefs, emotions and information. While culture is consolidated as a territory that is transformed by Communication, communicating also means putting into action a complex system of shared beliefs, values, customs and practices that define a group of people.